Data Identification in Current Population Accounting - A. V. Zhivitsa (Цифровая трансформация)
The article considers issues related to the use of data identiﬁers in current population accounting. The author’s classiﬁcation of methods for identifying personal data a with an indication of their advantages and disadvantages  is  presented.  The  dangers  of  using  identiﬁcation  numbers  are  deﬁned.  Particular  attention  is  paid to the problem of repeated formation of identiﬁcation numbers and ways to prevent it and stop the consequences. Proposals on the use of identiﬁcation numbers in the created information resources are formed.